The Physicochemical, Microbiology, and Sensory Characteristics of Kefir Goat Milk with Different Levels of Kefir Grain - Sulmiyati, Sulmiyati; Said, N. S.; Fahrodi, D. U.; Malaka, R.; Maruddin, F. (Tropical Animal Science Journal, 2019)
Kefir is a fermented milk product. The kefir grain starter consists of lactic acid bacteria and yeast that produce lactic acid and alcohol. The quality of kefir is strongly influenced by the type of milk used, the amount of kefir grain, kefir grain microorganisms, and the incubation period. The characteristics of goat-milk kefir with the addition of different amounts of kefir grain were studied by measuring pH value, ethanol content, and percentage of lactic acid. The experimental design was a completely randomized design (RCD) with three treatments and five replications. The treatments were performed by using different amounts of kefir grains i.e., 2%, 4%, and 6%. Goat-milk kefir was pasteurized at 105oC for 5 minutes, cooled at room temperature (37oC), and then kefir grain was added at different levels and incubated for 12 hours. The results showed that the amounts of kefir grain had a significant effect (p